2022
DOI: 10.1158/2326-6066.cir-21-0515
|View full text |Cite
|
Sign up to set email alerts
|

Reversing T-cell Exhaustion in Cancer: Lessons Learned from PD-1/PD-L1 Immune Checkpoint Blockade

Abstract: Anti–PD-1/PD-L1 immune checkpoint blockade (ICB) therapy has revolutionized the treatment of many types of cancer over the past decade. The initial therapeutic hypothesis underlying the mechanism of anti–PD-1/PD-L1 ICB was built around the premise that it acts locally in the tumor, reversing the exhaustion of PD-1hiCD8+ T cells by “releasing the brakes.” However, recent studies have provided unprecedented insight into the complexity within the CD8+ T-cell pool in the tumor microenvironment (TME). Single-cell R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(77 citation statements)
references
References 72 publications
2
74
0
1
Order By: Relevance
“…Identification of biomarkers of response to ICB relies on the understanding of the cellular and molecular mechanisms responsible for sensitivity or resistance of tumors to these therapies [ 1 ]. The adaptive T-cell response is the major target of PD-1/PD-L1 axis blockade and, understandably, most studies aiming to decipher resistance mechanisms and to identify biomarkers of response were focused on CD8 T cells, which directly recognize and kill tumor cells [ 24 ]. Whereas initial studies focused on the role of anti-PD-1/PD-L1 in reversing in situ terminal exhaustion of CD8 T cells, data obtained from preclinical tumor models and studies in cancer patients showed that responsiveness was dependent upon both reversal of exhaustion at the tumor site and proliferation of early exhausted peripheral CD8 T cells [ 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of biomarkers of response to ICB relies on the understanding of the cellular and molecular mechanisms responsible for sensitivity or resistance of tumors to these therapies [ 1 ]. The adaptive T-cell response is the major target of PD-1/PD-L1 axis blockade and, understandably, most studies aiming to decipher resistance mechanisms and to identify biomarkers of response were focused on CD8 T cells, which directly recognize and kill tumor cells [ 24 ]. Whereas initial studies focused on the role of anti-PD-1/PD-L1 in reversing in situ terminal exhaustion of CD8 T cells, data obtained from preclinical tumor models and studies in cancer patients showed that responsiveness was dependent upon both reversal of exhaustion at the tumor site and proliferation of early exhausted peripheral CD8 T cells [ 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive T-cell response is the major target of PD-1/PD-L1 axis blockade and, understandably, most studies aiming to decipher resistance mechanisms and to identify biomarkers of response were focused on CD8 T cells, which directly recognize and kill tumor cells [ 24 ]. Whereas initial studies focused on the role of anti-PD-1/PD-L1 in reversing in situ terminal exhaustion of CD8 T cells, data obtained from preclinical tumor models and studies in cancer patients showed that responsiveness was dependent upon both reversal of exhaustion at the tumor site and proliferation of early exhausted peripheral CD8 T cells [ 4 , 24 ]. Expansion of peripheral CD8 T cells takes place in lymph nodes and is dependent upon CD4 help [ 16 ], inferring the importance of CD4 T cells in response to ICB.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Tregs play a key role in suppressing the anti-tumoral immune response mediated by NK and CD8 + T cells [ 79 ]. In this context, recent reports have clearly shown the effectiveness of PD-1/PD-L1 checkpoint blockade in preventing anti-tumoral cytotoxic CD8+ T cell exhaustion [ 80 ] and counteracting the suppressive function of infiltrating Tregs leading to improved response to cancer therapy increase disease free survival [ 81 ]. However, in our model, Tregs were not significantly increased in tumors from obese mice ( Fig 3B and 3C ), similarly to what was observed in a previous study in melanoma [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of intratumor PD-1 Treg was known to suppress anti-tumor immunity (Palucka and Coussens, 2016). In addition, high abundance of CD8+T cells at exhausted state, which was featured with high Frontiers in Cell and Developmental Biology | www.frontiersin.org their high PD-1 expression, lost the proper effector response to eliminate tumor cells (Budimir et al, 2022). Taken together, PD-1/ PD-L1 blockade could confer better immune response in the low LR.…”
Section: Discussionmentioning
confidence: 99%